Investigation of Brand Name-Country of Origin Preference in Four Different Product Groups with Respect to Conspicuous Consumption Tendency - Doğan, Volkan; Özkara, Behçet Yalın (International Review of Management and Marketing, 2013)
The aim of this study is to examine different preferences for brand name–country of origin shaped in line with levels of conspicuous consumption tendency and to determine Turkish consumers’ preferences for brand name–country of origin combinations in different product groups. The study was conducted in Eskisehir (Turkey) with a sample of 413 people chosen through convenience sampling. The study data were collected with a questionnaire and face-face-to interviews. The participants’ preferences for brand name-country of origin combinations were determined separately based on four different product groups(hedonic, utilitarian, durable and non-durable). The study showed that, for all the four product groups, the participants preferred the products with a Turkish brand name and Turkey as the country of origin most, followed by the products with a French brand name and France as the country of origin. This finding suggests that, with respect to the four product groups in the study, Turkish consumers preferred domestic products over foreign products. Also, the participants who preferred French brand name-France as the country of origin for the hedonic product, French brand name-Turkey as the country of origin for the utilitarian product, French brand name-Turkey as the country of origin for the durable product and French brand name-France as the country of origin for the non-durable product were found to have highest tendency of conspicuous consumption in the corresponding product groups. In other words, as the level of conspicuous consumption increased, the participants tended to prefer French brand name-France as the country of origin for the hedonic product, French brand name-Turkey as the country of origin for the utilitarian product, French brand name-Turkey as the country of origin for the durable product and French brand name-France as the country of origin for the non-durable product. Keywords: Brand name; Country of origin; Congruence between brand name and country of origin; Conspicuous consumption JEL Classifications: M31